Vulnerability and Coping Strategies of Women in Disaster: A Study on Coastal Areas of Bangladesh - Islam, Md Rabiul (Arts Faculty Journal, 2012)
Natural disaster is a common phenomenon in Bangladesh. Almost every year Bangladesh suffers highly by different kinds of disasters like flood, tropical cyclones, tornados, tidal surges, droughts and large scale river erosion etc. Bangladesh is a low lying delta with very gentle slopes. It is located at the lowest end of the Ganges, Brahmaputra and Meghna Basin (Roy et al 2009). Bangladesh has special geographical feature. It has the Himalayan range to the north, the Bay of Bengal to the south with its funneling towards Meghna estuary and the vast stretch of Indian land to the west. These special geographical features have significant impact on the weather system of Bangladesh. Due to this weather system, Bangladesh is the worst victimized country of natural disasters which causes loss of lives and properties (Nizamuddin 2001). A large number of the total population of our country lives in the coastal areas. According to the population census 2001, the whole coastal area of the country has about 46 million people. The average size of the household is 7, the density of population is 743 per sq. km. Womenfolk are 49% of the coastal population, while 23% (8 million) are urban-dwellers, size of the labor force (15-59 years age group) is 18.6 million which are about 53% of the coastal population (BBS 2006). DOI: http://dx.doi.org/10.3329/afj.v4i0.12938 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.147-169